Penerapan Penelitian Tindakan Kelas Cooperative Learning Tipe Peer Teaching untuk Meningkatkan Keterlibatan Siswa Dalam Pembelajaran Biologi - Nory Shenta Dewi; Murni Ramli; Yudi Rinanto (BIO-PEDAGOGI, 2018)
The research aims to increase students' engagement in Biology learning by applying cooperative learning method specifically peer teaching. The subjects consisted of 32 high school students focusing on Low Achievement (LA) and High Achievement (HA) students. This research is classroom action research (CAR) with 3 Cycles. The research procedure includes the stage of reflection, planning, implementation of action and observation. Behavioral Engagement (BE) data obtained through observation, other data in the form of Psychological Engagement (PE) and Cognitive Engagement (CE) obtained through student engagement questionnaire based on Student Engagement Instrument (SEI). Technique of data validation used is triangulation technique. Technique of analysis data performed by data reduction, data presentation and drawing conclusions based on qualitative descriptive analysis. The results showed that cooperative learning method specifically peer teaching can increase student engagement in biology learning. The average percentage of all BE aspects observed in LA students before the treatment given, Cycle I, Cycle II and Cycle III respectively was 13.72%; 35.24%; 48.26% and 64.24% respectively. Meanwhile BE results of HA students before the treatment given, Cycle I, Cycle II and Cycle III respectively were 22.22%; 48.97%; 56.6% and 64.76% respectively. The results of PE of LA students before the treatment given to Cycle III increased by 3.54% while PE in HA students before the treatment given to Cycle III increased from 3.75%. The result of CE analysis of LA students has increased before the treatment given toward Cycle III that is 2.94% while in HA students increased by 2.95%.